2005
DOI: 10.1152/ajpheart.00462.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of F-actin organization in p38 MAP kinase-mediated apoptosis and necrosis in neonatal rat cardiomyocytes subjected to simulated ischemia and reoxygenation

Abstract: . Role of F-actin organization in p38 MAP kinase-mediated apoptosis and necrosis in neonatal rat cardiomyocytes subjected to simulated ischemia and reoxygenation. Am J Physiol Heart Circ Physiol 289: H2310 -H2318, 2005. First published July 22, 2005 doi:10.1152/ajpheart.00462.2005.-Activation of p38 mitogen-activated protein (MAP) kinase (MAPK) has been implicated in the mechanism of cardiomyocyte (CMC) protection and injury. The p38 MAPK controversy may be related to differential effects of this kinase on ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 55 publications
4
41
0
Order By: Relevance
“…Cytochalasin D is a fungal alkaloid that depolymerizes actin filaments by binding to the + end of F-actin thus blocking the addition of more units. It was used previously in the range of 1-40μM [45] to disrupt actin cytoskeleton in cardiomyocytes [46,47]. Our use of 2μM is consistent with those studies.…”
Section: Selection Of Topographical Cues Electrical Field Stimulatiosupporting
confidence: 88%
“…Cytochalasin D is a fungal alkaloid that depolymerizes actin filaments by binding to the + end of F-actin thus blocking the addition of more units. It was used previously in the range of 1-40μM [45] to disrupt actin cytoskeleton in cardiomyocytes [46,47]. Our use of 2μM is consistent with those studies.…”
Section: Selection Of Topographical Cues Electrical Field Stimulatiosupporting
confidence: 88%
“…Despite the increased p38 MAPK activity, cell viability was higher than control, suggesting that p38 MAPK activity is not completely related to transcription of apoptotic cell signaling. Recently, Okada et al (38) reported that p38 MAPK plays a differential role in cardiomyocytes, protecting or killing, depending on its role in signal transduction (38). A recent report (33) suggests that the p38 MAPK ␤-isoform is prosurvival.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the effects of inhibiting PVT1 expression on programmed cell death in cells with and without PVT1 amplification/overexpression by measuring membrane permeability (22), cell morphology, and F-actin reorganization (23, 24) using high-content image analyses. YO-PRO-1 dye uptake increases when cells lose membrane integrity during cell death, whereas F-actin reorganization results in increased Alexa Fluor 488-phalloidin binding that has been associated with earlier stages of apoptosis (24). Beginning at 8 h after transfection, siPVT1a significantly increased YO-PRO-1 dye uptake and F-actin staining relative to LipofectAMINE controls in HEY and CAOV4 cell lines in which PVT1 is amplified and overexpressed ( Fig.…”
Section: Resultsmentioning
confidence: 90%